War reporters under threat : the United States and media freedom - Paterson, Chris (Pluto Press, 2014)
Combines critical scholarship with investigative journalism to examine the US government threat to journalists, a threat ignored or dismissed to date.
Keywords: Freedom of the press : United States; War correspondents : Protection; War correspondents : Civil rights